Physicochemical, antioxidative and sensory properties of pre-treated sliced pear cultivar during frozen storage (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Pear is a typical fruit of temperate zones with high nutritive values and organoleptic properties, but when this fresh fruit being harvested, it will undergo chemical changes which can cause spoilage and product deterioration. Freezing could be as a preservative method to maintain quality attributes (colour, texture) of fresh produce that change over time. The purpose of this study is to determine ascorbic acid content and antioxidant activity of frozen fruit treated with osmotic solution. Pears were pre-treated with blanching, osmotic and both blanching and osmotic solution prior to freezing. Two varieties of pear fruit which are Asian pear and Packham pear were analyzed for physicochemical (colour and texture), antioxidative properties (ascorbic acid content, antioxidant activity and total phenolic content) and sensory acceptability. The pears were subjected to different pre-treatments prior to freezing such as blanching and osmotic solution during storage. The results showed that colour attributes of frozen pears were significantly affected by treatment which in contrast to texture properties of frozen pears during storage. Ascorbic acid content of frozen Packham pear was recorded the highest (6.38 ± 0.96 mg/100 g) after treated in osmotic solution compared to frozen Asian pear, the highest (4.62 ± 1.15 mg/100 g) was found in blanching treatment prior to storage, both tested after day 1 of storage. When treated in blanching treatment, the antioxidant activity of frozen Packham pear using DPPH assay exhibited (84.61 ± 0.69 %) contains high scavenging activity on day 1, while for Asian pear (67.63 ± 2.37 %) in blanching treatment on day 3. Using seven-point hedonic scale, sensory acceptability shows that frozen Asian pear treated in osmotic solution was highly rated among consumers with overall acceptance of 5.80 ± 0.85. Thus, combination of pre-treatment which were osmotic and blanching and freezing helps to retain the quality of frozen pears during period of storage.
Keywords: antioxidant; ascorbic acid; frozen; osmotic solution; pear